Transcriptomic Analysis Reveals Insights on Male Infertility in Octopus maya Under Chronic Thermal Stress - López-Galindo, Laura; Juárez, Oscar E.; Larios-Soriano, Ernesto; Del Vecchio, Giulia; Ventura-López, Claudia; Lago-Lestón, Asunción; Galindo-Sánchez, Clara (Frontiers in Physiology, 2019)
Octopus maya endemic to the Yucatan peninsula, Mexico, is an ectotherm organism particularly temperature-sensitive. Studies in O. maya females show that temperatures above 27 ºC reduce the number of eggs per spawn, fertilization rate and the viability of embryos. High temperatures also reduce the male reproductive performance and success. However, the molecular mechanisms are still unknown. The transcriptomic profiles of testes from thermally stressed (30 ºC) and not stressed (24 ºC) adult male octopuses were compared, before and after mating to understand the molecular bases involved in the low reproductive performance at high temperature. The testis paired-end cDNA libraries were sequenced using the Illumina MiSeq platform. Then, the transcriptome was assembled de novo using Trinity software. A total of 53,214,611 high-quality paired reads were used to reconstruct 85,249 transcripts and 77,661 unigenes with an N50 of 889 bp length. Later, 13,154 transcripts were annotated implementing Blastx searches in the UniProt database. Differential expression analysis revealed 1,691 transcripts with significant difference among treatments. Functional annotation and pathway mapping of differential expressed genes revealed significant enrichment for biological processes involved in spermatogenesis, gamete generation, germ cell development, spermatid development and differentiation, response to stress, inflammatory response and apoptosis. Remarkably, the genes such as ZMYND15, KLHL10, TDRD1, TSSK2 and DNAJB13, which are linked to male infertility in other species, were differentially expressed among the treatments. The expression levels of these key genes, involved in sperm motility and spermatogenesis were validated by quantitative real-time PCR. The results suggest that the reduction in male fertility at high temperature can be related to alterations in spermatozoa development and motility.